2009
DOI: 10.1039/b820819k
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic paramagnetic neutral gold dithiolene complexes

Abstract: The sulfiding of benzils with P(4)S(10) in 1,3-dimethyl-2-imidazolidinone (DMI) as solvent allows for a direct synthesis of neutral radical, gold dithiolene complexes based on 1,2-bis-(4-alkoxy-phenyl)ethylene-1,2-dithiolate ligands with n-butyl, n-octyl and n-dodecyl chains. The three neutral and soluble complexes Au-OC(4), Au-OC(8) and Au-OC(12) exhibit a near infrared (NIR) absorption band around 1.5 mum and EPR characteristics which confirm a strong delocalization of the spin density on the electron-rich d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 38 publications
6
57
0
Order By: Relevance
“…The next step of the reactions is the hydrolysis and then the formation of neutral complexes using metal carbonyl or other reactive salts, e.g., NiCl 2 , PdCl 2 (PhCN) 2 . The following Scheme 4 gives an example of the preparation of a series of complexes from the corresponding 1,2-diketones [44,60,65,68,89,98,101,110,111]. Scheme 4.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The next step of the reactions is the hydrolysis and then the formation of neutral complexes using metal carbonyl or other reactive salts, e.g., NiCl 2 , PdCl 2 (PhCN) 2 . The following Scheme 4 gives an example of the preparation of a series of complexes from the corresponding 1,2-diketones [44,60,65,68,89,98,101,110,111]. Scheme 4.…”
Section: Methodsmentioning
confidence: 99%
“…The IR vibrational spectra of [Ni(dt)(dmit)] indicate a dithioglyoxal structure (large HC-CH bond) in the dt ligand of this complex, rather than an olefinic structure (short HC-CH bonds) as in the edt ligand of [Ni(edt) 2 ] [49], and consequently, a push/pull behaviour in [Ni(dt)(dmit)] and similar compounds [48,89]. It is suggested that the molecular structure has a resonance form similar to that of the push/pull complexes [95].…”
Section: Structural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Thus, the introduction of additional carbons chains in the meta position of the phenyl rings destabilizes the formation of dimers and favors the formation of regular chains with uniform antiferromagnetic interactions. The large J value indicates strong intermolecular interactions, in line with a face-to-face stacking of the radical complexes in the crystalline state, with a favorable overlap between the dithiolene moieties.…”
Section: 22mentioning
confidence: 99%
“…Disodium maleonitriledithiolate (Na 2 mnt) was synthesized following the published procedure [24], and a similar process for preparation of 4-amino-1-hexylpyridinium bromide was used for the synthesis of 1,1'-didecyl-4,4'-bipyridinium dibromide [21]. Compound 1 was characterized by elemental analyses (C, H and N elements) and infrared spectrum in 400-4000 cm − 1 [25].…”
Section: Introductionmentioning
confidence: 99%